The Relationship between the Bhagavadgītā and the Vedic Upaniṣads: Parallels and relative chronology - Ježić, Mislav (2009)
Mislav Jezic The Bhagavadgī tā and the Vedic Upaniṣ ads: A survey of relationships and their implications for our understanding of the Great Epic Since Wilhelm von Humboldt’ s essay (1826) various text-historical analyses of the Bhagavadgī tā (BhG) have been undertaken by scholars in the West and in India. Good surveys are given by A. Malinar (1996), J. L. Brockington (1998), and – concentrated on one line of approach - by P. Szczurek (2002). In my analysis, partly published in 1979 and 1986, I tried to show that there are four main components of the BhG text: 1. BhG – epic episode (MBh): 1.1-47, 2.1-4, 9-10, 31-37, 2. BhG – the triṣ ṭ ubh hymn (independent text): 2.5-8, (81*), 11.15-50, 3. BhG – Upanişads (MBh), and 4. BhG – the bhakti synthesis (MBh) A closer look will show that litteral parallels between passsages in the BhG and those in older Vedic Upanişads can be found in chapters 2, 3 and 5, as well as 13 and 15, all in the upanişadic passages of the BhG (from an older and a younger group), and in chapter 8 embedded in the bhakti layer (in trişţubhs: it is proved in the paper that they belong to the triṣ ṭ ubh hymn (2)). The Upanişads that show litteral parallels with the BhG are notoriously the metrical Upanişads Kaţha and the Śvetā śvatara. If we establish the series of text layers of the BhG in their relative chronological order, these parallels may help us in determining the relative age of these layers with respect to the upanişadic texts: they imply what is most probably earlier in the BhG than the Kaţha and Śvetā śvatara passages, what is more or less simultaneous, and what is later. It helps us in understanding the process in which the BhG gained the status of one of the three prasthā nas of the later Vedā nta philosophy. It also has implications for the growth of the Kŗ şņ a’ s role as a teacher, and later as the god incarnated in the BhG, which deeply influenced the development of the Mahā bhā rata from a heroic epic about the battle at the Kurukşetra to a work with didactic contents, and finally to a work with religious significance.
Projekt MZOS
ENG